HUBUNGAN EFIKASI DIRI DENGAN INTERAKSI SOSIAL SISWA - Krisa Etik Nur Safitri; Dadang Kurnia; Rini Sri Indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Self-Efficacy Relationship with Student Social Interaction. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan Bogor University 2022. This research is quantitative research with a correlation approach. This research aims to find out the relationship of self-efficacy with social interaction class V Pabuaran State Elementary School 07 Cibinong District Bogor Regency. The population of the study was 78 students with a sample number of 44 students. This study was conducted in the odd semester of the 2021/2022 school year based on the results of the analysis obtained the path coefficient (rxy) 0.408 in the pattern Ŷ = 54.21 + 0.449x which means the level of relationship in this study is relatively low. The magnitude of the relationship of self-efficacy with the social interaction of students is indicated in the coefficient of determination (r²) of 0.17 or 17% and the remaining 83% is determined by other factors. The calculation of hypothesis testing resulted in thitung 2,895 > ttabel 2,085 with a real level of 0.05 so that it can be concluded that there is a positive and significant relationship between self-efficacy and social interaction of students in students of class V of Pabuaran State Elementary School 07 Cibinong District of Bogor Odd Semester of The Academic Year 2021/2022.